QUESTIONING STRATEGIS USED BY ENGLISH TEACHER DURING CLASSROOM INTERACTION AT EIGHTH GRADE OF SMP NEGERI 1 TELUKDALAM - Princess Destrry Laia; Senadaman Wau; Restu Damai Laia; Mohamad Yunus Laia (Research on English Language Education, 2022)
This research aimed at finding and describing types of questioning strategies used by English teacher. This research was designed by using qualitative descriptive method. The instruments of data collection were observation and interview. After analyzing the data, researcher found that the questioning strategies were used by English teacher during classroom interaction. The questioning strategies used were: (1) procedural question, (2) convergent question, (3) divergent question. Furthermore, the purposes English teacher used questioning strategies were: (1) to make sure that the students were in good health and the students’ readiness before starting the lesson, (2) to attract students’ concentration, (3) as effort to achieve the learning objectives, (4) as the stimulus to think critically (5) as the effort to provide opportunities to express the ideas. Therefore, researcher concluded that questioning strategies used by English teacher was to know how far students understood about the material and to make sure whether the learning objectives have been achieved or not. Furthermore, the researcher suggests that English teacher could use questioning strategies to elicit students’ response during teaching and learning process.